The Role of Traditional Opinion Leaders in Political Decision-Making: A Case Study of Coastal Communities in Eastern Indonesia - Hamid, Ihsan (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This research examines the dynamics of opinion leadership in political decision-making within the coastal community of Lembar Selatan Village, Indonesia. The study specifically investigates the characteristics of opinion leaders, their communication patterns, and their influence on community political choices. Using a qualitative descriptive approach, data were collected through in-depth interviews and participant observations involving key community leaders and residents. The findings reveal that opinion leadership is primarily concentrated in formal and informal community figures, notably a former Village Head who also served as a member of the Regional People's Representative Council (DPRD). These leaders employ interpersonal communication strategies to disseminate political information and shape public opinion regarding candidates and policies. The study demonstrates that opinion leaders serve as crucial intermediaries in political communication, functioning as both motivators and guides in the community's political decision-making process. This research contributes to understanding the role of traditional leadership structures in local political communication within coastal communities of developing regions.